ECONOMIC GROWTH AND POVERTY: THE MODERATING EFFECT OF INCOME INEQUALITY - Istiqomah, Istiqomah; Floresti, Dwita (Faculty of Economics and Business, University of Pasundan, 2024)
The trickle-down effect assumes that the progress of a group of people will automatically trickle down, thus creating jobs which in turn will promote the necessary conditions for equitable economic growth. However, previous studies on the association between economic growth and poverty have shown inconclusive results.This study fills the gap of the above research differences by introducing income inequality as a moderating variable in the relationship between economic growth and poverty. Secondary data from 34 provinces in Indonesia during 2016-2020 period were analyzed using panel data moderated regression. The results showed that while simple linear regression model indicates positive significant effect of economic growth on poverty, the interaction between economic growth and income inequality shows negative significant effect on poverty. This paper concludes that income inequality as measured by the Gini index moderates the effect of economic growth on poverty which supports the importance of inclusive economic growth.